2023
DOI: 10.3390/cancers16010125
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Promotes Cisplatin Resistance in Bladder Cancer via Beclin1 Deacetylation-Mediated Autophagy

Yan Sun,
Xudong Liu,
Hang Tong
et al.

Abstract: Autophagy-dependent cisplatin resistance poses a challenge in bladder cancer treatment. SIRT1, a protein deacetylase, is involved in autophagy regulation. However, the precise mechanism through which SIRT1 mediates cisplatin resistance in bladder cancer via autophagy remains unclear. In this study, we developed a cisplatin-resistant T24/DDP cell line to investigate this mechanism. The apoptosis rate and cell viability were assessed using flow cytometry and the CCK8 method. The expression levels of the relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…SIRT1 upregulation has already been demonstrated in some cancer cells, such as esophageal squamous cell carcinoma (ESCC), lung cancer, and colon cancer (Hong and Pyo, 2018;Ma et al, 2018;Guo et al, 2021;Otsuka et al, 2022). Furthermore, increased expression of SIRT1 has been found to confer resistance to cisplatin in cancer cells (Cao et al, 2015;Wang et al, 2022;Sun et al, 2023). Moreover, research has demonstrated that H 2 S can enhance the expression of SIRT1 by facilitating its S-sulfhydration (Wu et al, 2023), which involves altering the Cys residues on the target protein to convert the sulfhydryl group (R-SH) into a persulfide group (R-SSH).…”
Section: Discussionmentioning
confidence: 98%
“…SIRT1 upregulation has already been demonstrated in some cancer cells, such as esophageal squamous cell carcinoma (ESCC), lung cancer, and colon cancer (Hong and Pyo, 2018;Ma et al, 2018;Guo et al, 2021;Otsuka et al, 2022). Furthermore, increased expression of SIRT1 has been found to confer resistance to cisplatin in cancer cells (Cao et al, 2015;Wang et al, 2022;Sun et al, 2023). Moreover, research has demonstrated that H 2 S can enhance the expression of SIRT1 by facilitating its S-sulfhydration (Wu et al, 2023), which involves altering the Cys residues on the target protein to convert the sulfhydryl group (R-SH) into a persulfide group (R-SSH).…”
Section: Discussionmentioning
confidence: 98%